Clinical Effects of Mercury in Conservative Dentistry: A Systematic Review, Meta-Analysis, and Trial Sequential Analysis of Randomized Controlled Trials - Romeo Patini; Gianrico Spagnuolo; Federica Guglielmi; Edoardo Staderini; Michele Simeone; Andrea Camodeca; Patrizia Gallenzi (Hindawi Limited, 2020)
Background and Purpose. Following the new directives of the European Union, which foresee the amalgam ban, the debate on its hypothetical toxicity has started again. So, the aim of this systematic review is to definitively evaluate the eventual effects of the exposure to Hg in adults and children with and without dental amalgam fillings measuring the Hg concentration in various biological fluids. Methods. A systematic literature search was conducted in four electronic databases (Ovid via PubMed, Web of Science, Scopus, and CENTRAL) including all available randomised controlled trials published in the last 15 years comparing the use of dental amalgam with composite resins in humans with a follow-up period of at least one year. The primary outcome was the Hg concentration in biological fluids (urine, hair, blood, and saliva) with the aim of assessing their reliability as biomarkers of Hg exposure. The risk of bias was assessed through the Cochrane Collaboration tool and the overall quality of evidence through the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) system. The results of the meta-analysis were expressed using a random-effects model, and their power was assessed through the trial sequential analysis (TSA). Results. From the initial 2555 results, only 6 publications were included in the review: five were considered as having high risk of bias, whereas one as having moderate risk. Only two articles were eligible for quantitative analysis. The meta-analysis gathered data from 859 patients but was nevertheless not significant (p = 0.12). The TSA confirmed this evidence revealing that it was due to a lack of statistical power since the required information size (RIS) threshold is not reached. Conclusions. The existing evidence revealed that there are not enough data to support the hypothesis that restorations with dental amalgam can cause nephrotoxicity when compared with composite resins restorations.